The N‐terminal peptide of the transglutaminase‐activating metalloprotease inhibitor from Streptomyces mobaraensis accommodates both inhibition and glutamine cross‐linking sites. (29th August 2019) - Juettner, Norbert E.; Schmelz, Stefan; Anderl, Anita; Colin, Felix; Classen, Moritz; Pfeifer, Felicitas; Scrima, Andrea; Fuchsbauer, Hans‐Lothar
Abstract : Streptomyces mobaraensis is a key player for the industrial production of the protein cross‐linking enzyme microbial transglutaminase (MTG). Extra‐cellular activation of MTG by the transglutaminase‐activating metalloprotease (TAMP) is regulated by the TAMP inhibitory protein SSTI that belongs to the large Streptomyces subtilisin inhibitor (SSI) family. Despite decades of SSI research, the binding site for metalloproteases such as TAMP remained elusive in most of the SSI proteins. Moreover, SSTI is a MTG substrate, and the preferred glutamine residues for SSTI cross‐linking are not determined. To address both issues, that is, determination of the TAMP and the MTG glutamine binding sites, SSTI was modified by distinct point mutations as well as elongation or truncation of the N‐terminal peptide by six and three residues respectively. Structural integrity of the mutants was verified by the determination of protein melting points and supported by unimpaired subtilisin inhibitory activity. While exchange of single amino acids could not disrupt decisively the SSTI TAMP interaction, the N‐terminally shortened variants clearly indicated the highly conserved Leu40‐Tyr41 as binding motif for TAMP. Moreover, enzymatic biotinylation revealed that an adjacent glutamine pair, upstream from Leu40‐Tyr41 in the SSTI precursor protein, is the preferred binding site of MTG. This extension peptide disturbs the interaction with TAMP. The structure of SSTI was furthermore determined by X‐ray crystallography. While no structural data could be obtained for the N‐terminal peptide due to flexibility, the core structure starting from Tyr41 could be determined and analysed, which superposes well with SSI‐family proteins. Enzymes: Chymotrypsin, EC3.4.21.1 ; griselysin (SGMPII, SgmA), EC3.4.24.27; snapalysin (ScNP), EC3.4.24.77 ; streptogrisin‐A (SGPA), EC3.4.21.80 ; streptogrisin‐B (SGPB), EC3.4.21.81 ; subtilisin BPN', EC3.4.21.62 ; transglutaminase, EC2.3.2.13 ; transglutaminase‐activating metalloprotease (TAMP), EC3.4.‐.‐; tri‐/tetrapeptidyl aminopeptidase, EC3.4.11.‐; trypsin, EC3.4.21.4 . Databases: The atomic coordinates and structure factors (PDB 6I0I) have been deposited in the Protein Data Bank (http://www.rcsb.org ). Abstract : The subtilisin inhibitory protein from Streptomyces mobaraensis is equally a strong inhibitor of the transglutaminase‐activating metalloprotease and a substrate of transglutaminase. Aim of the study was the determination of binding sites for both enzymes by site‐directed amino acid substitutions and N‐terminal modification of the inhibitory protein. The investigation revealed two N‐terminal sequence motifs of the inhibitory protein, Gln37‐Gln38 and Leu40‐Tyr41, allowing interaction with transglutaminase and its activating metalloprotease.